Sulla pedagogia di Ferrante Aporti: note - Franco Cambi (Firenze University Press, 2011)
The author, in his essay, reflects the importance of the work done by the priest of Cremona. He carefully read the writings of some scholars specialize on Aporti (for example Christina Sideri) and he is able to say that these extensive studies show a more complete Aporti. Aporti seems like a sophisticated renaissance educator, a man sensitive to the treatment of childhood and at the same time apolitically committed man, that binds to the positions of the Catholic-liberal. An important educator to read and study with more and more attention.